Get the information you need with the help of IDNLearn.com's extensive Q&A platform. Find accurate and detailed answers to your questions from our experienced and dedicated community members.
Which equation written below in vertex form is
equivalent to the equation y=x²-6x+12?
y=(x-3)²
y=(x-6)² + 12
y= (x+3)² +3
y=(x-3)² +3
Sagot :
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com is committed to providing accurate answers. Thanks for stopping by, and see you next time for more solutions.